Politeness strategies in children’s English learning media: A pragmatic analysis of VOA learning English video - Nada Nisrina Putri; Nina Sofiana (Journal of Research on English and Language Learning (J-REaLL), 2026)
Politeness is an essential aspect of pragmatic competence that enables learners to use language appropriately in different social contexts. While previous studies have primarily focused on politeness strategies in classroom-based teacher–student interactions, research on politeness within digital learning environments for children remains limited. This study addresses this gap by examining the use of politeness strategies in children’s English learning media through the VOA learning English (Let’s Learn English - Level 1 series), with particular attention to their functions in supporting instructional interaction in a digital learning context. A descriptive qualitative approach was employed using a pragmatic analysis framework grounded in politeness theory. Spoken utterances were transcribed, categorized into the four types of politeness strategies, and interpreted in terms of their contextual meanings. The findings indicate that all four politeness strategies are present in the videos, with positive politeness being the most dominant, followed by bald on-record, negative politeness, and off-record strategies. The frequent use of positive politeness reflects the instructor’s efforts to foster closeness, encouragement, and emotional support, which support children’s motivation and confidence in learning English. Although this study is limited to beginner-level VOA episodes, it demonstrates that politeness strategies in digital media can model social communication skills. Practically, integrating pragmatic elements into multimedia language instruction can enhance character building and polite communication behaviors. Future research could explore politeness strategies in other digital learning platforms, learners at intermediate and advanced levels of English proficiency, or cross-cultural contexts to further investigate pragmatic competence in online language education.